PEMANFAATAN BUNGA ROSELLA (Hibiscus sabdariffa L.) PADA OLAHAN PUDING SEBAGAI ALTERNATIF PANGAN FUNGSIONAL UNTUK KESEHATAN TUBUH - Wisnu Kusuma, Eka; Dhurhania, Crescentiana Emy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Rosella flowers can be used in the form of food and drinks that are beneficial for health. The anthocyanin content in Rosella flowers can be used as a natural dye and also as an antioxidant. The purpose of the Community Service activity is to utilize rosella flowers to increase health immunity and use natural ingredients as nutritious food to reduce high blood pressure. The methods used in this community service activity are socialization methods, questionnaires and pudding making practices. The activity went well and smoothly according to the series of activity schedules listed in the agenda. Increased public knowledge about the material from the pretest value from the previous 89.17% to 95.83%. The level of public satisfaction with the implementation of the activity was 96% so it can be concluded that the public is satisfied with the implementation of the Community Service activity.